مراعاة النظير في القرآن الكريم -دراسة بلاغية- - بدر الدين, عباس (جامعة الوادي university of eloued, 2023)
هذا البحث بعنوان مراعاة النظير في القرآن الكريم –دراسة بلاغية- وهو يعالج إشكال دور مراعاة النظير في بلاغة القرآن الكريم، ولمعالجة هذه الإشكالية سلكنا الخطة الآتية: البلاغة والبديع، مراعاة النظير في الدرس البلاغي، وجوه ودلالات مراعاة النظير وإعجازه في القرآن الكريم. وقد توصلنا إلى نتائج أهمها: مصطلح مراعاة النظير هو من المحسنات المعنوية لعلم البديع ويعبر عنه بالتناسب والتلاؤم بين الألفاظ والمعاني. وهذا الموضوع يزيد في الكلام قوة وجمالا. وبعد دراسة بعض الآيات القرآنية وجدنا أن وجوه هذا المصطلح متحققة في القرآن الكريم وهي تعمل على تلاؤم ألفاظه، تناسق معانيه، ترابط نظمه وبيان إعجازه.This research is entitled "Consideration of the counterpart in the Holy Quran". Quran -rhetorical study- It addresses the problem of the role of consideration of the counterpart in the Holy Quran and its rhetoric.so as to address this problematic، we do the following plan as follows: rhetoric and beautified tools، considering the counterpart in the less of rhetoric، considering the types and indications of the Holy Quran. We concluded that the term "Consideration of the counterpart" is the moral improvements for the science of "beautified tools". It expresses the alignment and consistency between words and meanings. This topic adds more power and beauty. To study some Quranic verses، we found that this type of this term is exist in the Holy Quran which leads to consistency of words، meanings and its alignment.
لغة
Keywords: مراعاة النظير، البلاغة، البديع، القرآن الكريم، الإعجاز; consideration of the counterpart، rhetoric، beautified tools، Holy Quran، miracle.